Bridging Efficacy of Tofacitinib Immediate‐Release to Extended‐Release Formulations for Treatment of Ulcerative Colitis: Application of a Model‐Informed Drug Development Approach. Issue 8 (13th May 2022) - Mukherjee, Arnab; Tsuchiwata, Shinichi; Chang, Cheng; Nicholas, Timothy; Su, Chinyu; Le, Vu H.; Kushner, Joseph; Kulisek, Nicole
Abstract: Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis (UC). We report a model‐informed drug development approach for bridging efficacy from immediate‐release (IR) to extended‐release (XR) tofacitinib formulations in patients with UC. IR‐XR efficacy bridging was supported by exposure‐response analysis of phase 3 induction/maintenance studies of the IR formulation in UC to identify exposure metrics relevant for efficacy. Pharmacokinetic studies in healthy subjects were used to confirm similarity of relevant exposure metrics of tofacitinib IR 5 mg twice daily to XR 11 mg once daily, and tofacitinib IR 10 mg twice daily to XR 22 mg once daily, thereby bridging efficacy between IR and XR formulations. Food effect was evaluated at both XR formulation dose levels. Exposure‐response analysis demonstrated that area under the plasma concentration–time curve (average plasma concentration) was a relevant predictor of efficacy. Pharmacokinetic studies demonstrated that area under the plasma concentration–time curve was equivalent between formulations under single‐dose and steady‐state conditions, and other exposure metrics were also similar. These results also supported bridging of safety data for IR‐XR formulations. Food had no impact on tofacitinib XR exposure. These data support efficacy/safety bridging of IR‐XR formulations in patients with UC.